The Effect of Fermented Jicama Extract with Lactobacillus plantarum B1765 as the Culture Starter on the Product Quality and Flavonoid Contents - Salsabila, Widi; Wikandari, Prima Retno (Jurnal Pijar Mipa, 2024)
Jicama (Pachyrhizus erosus) is a functional food containing phenolic compounds, with the main compounds being flavonoids. However, the presence of polyphenol oxidase and the structure of flavonoid compounds are still bound in the form of glycosides, so the bioactivity of jicama is not maximized. This study aims to determine the effects of jicama extract fermentation on product quality and increased flavonoid content in jicama. Fermentation was performed for 0, 12, 24, and 36 hours with 5% (v/v) of the starter culture, Lactobacillus plantarum B1765, at 37ºC. The result showed that fermentation times could increase Total Lactic Acid Bacteria (LAB), Total Tertitrable Acid (TTA), Total Phenolic Content (TPC), and Total Flavonoid Content (TFC). It also influenced a decrease in pH. The total LAB count was determined using the Total Plate Count method, the Total Tertitrable Acid was determined using acid-base titration, and the pH was determined using a pH meter. Total Phenolic Content was measured using the Folin-Ciocalteu method, and Total Flavonoid Content was measured using AlCl3 and potassium acetate. The analysis of the data revealed that jicama extract fermented optimum after 24 hours, with a total LAB count of 9.7x107±0.31 CFU/mL, a pH value of 4.21±0.22, a TTA of 0.376±0.025%, but TPC and TFC still increasing until 24 hours of fermentation to 16.22±0.312 mg GAE/g, and of 29.01±0.641 mg QE/g respectively. Fermentation of jicama extract with Lactobacillus plantarum B1765 increased total phenolic and total flavonoid contents and could be used as a functional food product.